2016
DOI: 10.1200/jco.2015.64.1076
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Adjuvant Chemotherapy for Locally Advanced Bladder Cancer

Abstract: In this observational study, adjuvant chemotherapy was associated with improved survival in patients with locally advanced bladder cancer. Although neoadjuvant chemotherapy remains the preferred approach based on level I evidence, these data lend further support for the use of adjuvant chemotherapy in patients with locally advanced bladder cancer postcystectomy who did not receive chemotherapy preoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
80
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(88 citation statements)
references
References 33 publications
1
80
1
1
Order By: Relevance
“…29 An observational study evaluated 5,653 patients, of which 23% received adjuvant chemotherapy after cystectomy. 28 Patients who received adjuvant chemotherapy had an improved OS (HR, 0.70; 95% CI, 0.06-0.76). 28 Although evidence for adjuvant therapy is not as strong as for neoadjuvant therapy, the growing body of data support the administration of adjuvant chemotherapy for patients with a high risk for relapse who did not receive neoadjuvant therapy.…”
Section: Adjuvant Chemotherapymentioning
confidence: 99%
See 2 more Smart Citations
“…29 An observational study evaluated 5,653 patients, of which 23% received adjuvant chemotherapy after cystectomy. 28 Patients who received adjuvant chemotherapy had an improved OS (HR, 0.70; 95% CI, 0.06-0.76). 28 Although evidence for adjuvant therapy is not as strong as for neoadjuvant therapy, the growing body of data support the administration of adjuvant chemotherapy for patients with a high risk for relapse who did not receive neoadjuvant therapy.…”
Section: Adjuvant Chemotherapymentioning
confidence: 99%
“…Studies have shown that adjuvant chemotherapy may delay recurrences and improve OS, [27][28][29] but no randomized comparisons of adequate sample size have definitively shown a survival benefit, in large part due to poor accrual. 30 Clinical trials of adjuvant chemotherapy with cyclophosphamide, doxorubicin, and cisplatin (CAP); MVAC; and methotrexate, vinblastine, epirubicin, and cisplatin (MVEC) regimens have each suggested a survival advantage.…”
Section: Adjuvant Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…The results found an improvement in OS with the use of adjuvant chemotherapy compared with RC alone (HR: 0.77; 95% CI: 0.59-0.99; p = 0.049), as well as an improvement in disease-free survival (DFS; HR: 0.66; 95% CI: 0.45-0.91) that was weighted toward the patients with node-positive disease (p = 0.010). More recently, Galsky and colleagues published their findings of a meticulous observational study of 'real-world' patients receiving adjuvant chemotherapy for high-risk MIBC, defined as pT3-4 and/or pathologically node positive [34]. Data from the National Cancer Data Base (NCDB) were used to compare OS for 5653 patients receiving adjuvant chemotherapy (23% of total) versus observation after curative-intent surgery.…”
Section: • Adjuvant Chemotherapymentioning
confidence: 99%
“…[2][3][4] Clinical trials exploring adjuvant chemotherapy have been flawed and/or underpowered, but accumulating evidence also supports an improvement in outcomes with this approach. [5][6][7] Unfortunately, once bladder cancer has visibly metastasized to distant sites, although systemic chemotherapy may impart therapeutic benefit, patients rarely achieve cure, and median survival is only approximately 14 months. 8 The standard management of patients with clinically localized and distant metastatic bladder cancer has been defined through a series of prospective randomized controlled trials.…”
Section: Introductionmentioning
confidence: 99%